Man at 25 : policy perspectives (Lagos : Manufacturers association of Nigeria, 1966)
This book is a chronicle of the association's endeavors in affecting government policies in the first twenty-five years of its existence.
Includes bibliographical references
ahz 14/03/2019
Loans
Keywords: Production economics; Nigeria